The Determination of A Place of Popular Tourism on The Island of Madura Using Weighted Product (WP) - Putro, Sigit Susanto; Rochman, Eka Malasari; Rachmad, Aery (Elinvo (Electronics, Informatics, and Vocational Education), 2023)
This research explored the diverse aspects of Madura Island, including its cultural, societal, and touristic facets. The primary focus was on developing a recommendation system to identify Madura's most popular tourist destinations. Utilizing the Weighted Product (WP) method, a decision support system model, this study assessed the popularity of various tourist attractions in Madura, aiding tourists in selecting destinations through a multi-criteria weighting process. Key parameters included the number of both foreign and local visitors, proximity to the city center, and visitor ratings. The study encompassed 62 tourist sites across four districts in Madura, evaluating the most popular attractions in each. Findings revealed the top destinations in each district: Bangkalan featured Makam Syeichona Cholil (preference value: 0.113), Sampang showcased Hutan Kera Nepa (0.127), Pamekasan highlighted Batu Ampar (0.171), and Sumenep was known for Makam Asta Tinggi (0.076). This research offered valuable insights for both tourists and stakeholders in the tourism industry of Madura Island.